Calaccitrera nandanatattva - Bandyopādhyāẏa, Pārthapratima. (Kalikātā : Utthaka Prakāśanī : Paribeśaka Ryāḍikyāla Impreśana, 1992)
Articles on the aesthetics of cinema; with reference to Indian films.
In Bengali.
Mode of access: Internet.
Keywords: Motion pictures -- India -- Aesthetics